(untitled) - Childers, Erskine (Sweden, 1994)
The purpose of this book is to identify the most important improvements needed to make what is supposed to be a system actually function as a system. The study proceeded from the premise that what will ultimately be needed, major constitutional transformation of the disparate elements into an integrated UN, is not attainable now. The study therefore addresses less radical alternatives, most of which are the irreducible minimum needed to enable the system to face the enormous challenges which now confront it. The study takes account of the many highly qualified commentators from many different cultures who have made proposals for improvement and restructuring. The main text of the study is intended for a wide readership of those who are interested in international organization and in the strengthening of the international system. Some entirely new features are proposed, including an Executive Committee for the system, a UN Parliamentary Assembly and a UN Council on Diversity, Representation and Governance. Also urged is extensive decentralization from global headquarters into the various regions of the world.
Keywords: United Nations